Rice (Oryza sativa) Protoplast Isolation and Its Application for Transient Expression Analysis. Issue 2 (10th June 2016) - He, Feng; Chen, Songbiao; Ning, Yuese; Wang, Guo‐Liang
Abstract: Rice ( Oryza sativa ) is not only the staple food for half of the world's population but also a model monocot plant for molecular biology studies. Although rice genes have been extensively investigated in the last two decades, the functions of many genes in the rice genome are still not known. One of the rapid and efficient approaches for determining gene function in vivo is protoplast‐based transient expression analysis. We established a rice protoplast system about 10 years ago, which has been recently used in many laboratories. This protocol is useful for protein expression, subcellular localization, bimolecular fluorescence complementation, and co‐immunoprecipitation assays. © 2016 by John Wiley & Sons, Inc.